A low cost electromagnetic sensor for detecting holes in metallic sheet - Galang P. N. Hakim; Ahmad Firdausi; Mudrik Alaydrus (Universitas Ahmad Dahlan, 2019)
Unwanted hole in metal sheet that use for vehicle body or structure is proved dangerous situation. To prevent disaster this hole needs to be found before its installation, or other wise it will be time and money consuming once its found when already finished installation. Therefore, an inspection using sensor for metal sheet is recommended to prevent this problem. In this paper, we proposed a new sensor using radio wave propagation to detect holes in metal sheet. We propose to use RSSI methods to detect hole based on electromagnetic wave propagation signal strength. Using this method we success to detect 8mm hole diameter in metal sheet with 1mm thickness. Using this method, we transmit electromagnetic wave energy at about 20 dBm, and we receive with average -27.53 dBm for iron sheet and -23.13 dBm for aluminum sheet.